2015
DOI: 10.1044/2015_ajslp-14-0161
|View full text |Cite
|
Sign up to set email alerts
|

Core-Lexicon and Main-Concept Production During Picture-Sequence Description in Adults Without Brain Damage and Adults With Aphasia

Abstract: We report the development of a core lexicon, differences in core-lexicon usage between speakers, and the relationship between core-lexicon and main-concept scores. Research is needed to determine the clinical utility and psychometric properties of these discourse measures and their potential contribution to multilevel discourse analysis of functional communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 41 publications
5
82
0
Order By: Relevance
“…[23][24][25][26][27] Dalton and Richardson analyzed responses to the Broken Window picture description task from the AphasiaBank discourse protocol. 7 They created a core lexicon (CoreLex) list of the 24 unique lemmas (word roots, such as "run" for "runs," "running" and "ran") used by at least 50% of the normative sample (92 control participants). When transcripts from 235 PWAs were analyzed to see how many of those 24 CoreLex words were used in their picture descriptions, results revealed significant differences between PWAs and controls as well as between all aphasia subtypes.…”
Section: For Morementioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25][26][27] Dalton and Richardson analyzed responses to the Broken Window picture description task from the AphasiaBank discourse protocol. 7 They created a core lexicon (CoreLex) list of the 24 unique lemmas (word roots, such as "run" for "runs," "running" and "ran") used by at least 50% of the normative sample (92 control participants). When transcripts from 235 PWAs were analyzed to see how many of those 24 CoreLex words were used in their picture descriptions, results revealed significant differences between PWAs and controls as well as between all aphasia subtypes.…”
Section: For Morementioning
confidence: 99%
“…When transcripts from 235 PWAs were analyzed to see how many of those 24 CoreLex words were used in their picture descriptions, results revealed significant differences between PWAs and controls as well as between all aphasia subtypes. CoreLex lists are also available for the Cat Rescue and Refused Umbrella tasks, 7 and will soon be available for the Cinderella story. Again, these materials can be found at the Discourse Analysis link on the AphasiaBank website.…”
Section: For Morementioning
confidence: 99%
See 1 more Smart Citation
“…Dalton and Richardson measured informativeness in discourse by analyzing CoreLex and main concepts (MCs) in transcripts from 166 controls and 235 PWA doing one of the Apha-siaBank picture description tasks (Broken Window). 9 Stems (or lemmas) produced by 50% or more of the controls were included in the CoreLex. Results indicated that PWA had significantly lower CoreLex scores and MCs than controls.…”
Section: Studiesmentioning
confidence: 99%
“…4 Indeed, research examining CoreLex indicates that PWAs produce fewer typical lexical items than controls. [5][6][7][8] CoreLex has demonstrated sensitivity to age-related differences in neurologically healthy individuals, 9 between healthy individuals and PWAs, and between aphasia subtypes. 7,8 CoreLex also correlated with performance on standardized assessments and other discourse measures.…”
mentioning
confidence: 99%